Agricultural Extension Services and Technology Adoption Survey, 2016 - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This study contains data that were collected to assess the demand and supply of extension services in Malawi. The survey covers 3001 households and 299 sections in all 29 districts in Malawi (excluding Likoma). These surveys were complemented by follow-up visits and in-depth interviews with farmers in four communities and interviews with more than 30 key informants at national, district, EPA, and section levels The data collected include information about the household and head; agricultural practices and production by plot; sales and utilization by crops, tree crops, livestock and fisheries; technology adoption; extension services; access to inputs and credit; social networks; food security and dietary diversity; non-food expenditure; and other measures of economic and social welfare.